THE EFFECT OF USING DIFFERENT TYPES OF OIL IN FEED ON THE CARCASSES COMPOSITION AND FAT DISTRIBUTION OF NATIVE CHICKEN - I P.E., Dewantara; Sukada, I K.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
This study aimed to determine the physical composition of the carcass and fat distribution of native chicken. The study used a completely randomized design (CRD), with 5 treatments and 4 replications. Each replication used 3 native chickens so that a total of 60 native chickens were used. The feed treatment (R) consisted of: R0: The feed without using oil, R1: The use of 3% palm oil in the feed, R2: The use of 3% used cooking oil in the feed, R3: The use of 3% fish oil in the feed, and R4: The use of 3% lard in feed. Variables observed included slaughter weight, carcass weight, percentage of carcass physical composition (meat, skin, and bone), and percentage of abdominal fat distribution (padding fat, mesentery fat, and ventriculus fat). The results showed that the use of 3% lard in feed produced the highest and significantly different mean on the variables of slaughter weight and carcass weight. The use of different types of oil in feed showed significant results on the percentage of abdominal fat distribution but did not affect the percentage of the physical composition of the carcass of native chickens. From the results of this study, it can be concluded that the use of 3% lard in feed can increase the slaughter weight and carcass weight of native chickens and the use of 3% palm oil, used cooking oil, fish oil, and lard in feed can increase the distribution of abdominal fat in native chickens. Key words: Native chicken, type of oil, carcass, fat distribution